Analisis Sentimen Terhadap Kontroversi Putusan MK Mengenai Usia Capres-Cawapres Menggunakan Multi-Layer Perceptron Dengan Teknik SMOTE - Sasmita, Sasmita; Jariah S.Intam, Rezki Nurul; Surianto, Dewi Fatmarani; B, Muhammad Fajar (LPPM, 2024)
In October 2023, the Constitutional Court's decision on age limit requirements for presidential and vice-presidential candidates stirred controversy, perceived as favoring a specific vice-presidential candidate. Public reactions flooded social media platforms, particularly on Najwa Shihab's YouTube channel, where sentiment analysis was conducted on 505 comments under the video titled